Profile of Students Mathematical Understanding through Diagnostic Tests Viewed from Multiple Intelligences - Ika Mulia Diarni; M. Ikhsan; Bintang Zaura; Rahmah Johar; Mailizar Mailizar (Universitas Syiah Kuala, 2023)
Mathematic has characteristics of abstract objects, so mathematical understanding is needed in studying mathematics. Until now, no research has examined students mathematical understanding viewed from multiple intelligences. This study aims to determine the profile of students mathematical understanding through diagnostic tests reviewed from multiple intelligences. This was a quantitative approach with population of all students in one of the junior high schools in Banda Aceh, Indonesia, and sample was 44 students selected by purposive sampling. Data collection was carried using multiple intelligence questionnaire and mathematical understanding test. Data analyzed using descriptive statistics. The results showed that students with mathematical logic intelligence able to define concepts verbally, interpret, identify, and distinguish concepts; students with linguistic, naturalistic, and existential intelligence able to define concepts verbally, interpret, and distinguish concepts; students with musical and kinesthetic intelligence able to define concepts verbally and interpret concepts; students with spatial intelligence able to interpret, identify, and distinguish concepts; and students with interpersonal intelligence able to interpret and distinguish concepts. The implication of this research is that teachers need to understand and realize that students' multiple intelligences are an important aspect that needs to be considered in delivering class material to improve students' mathematical understanding.